Rare occurrence of cryptic 5’ splice sites by downstream 3’ splice site/exon boundary mutations in a heavy-ion-induced egy1-4 allele of Arabidopsis thaliana - Sanjaya, Alvin; Nishijima, Ryo; Fujii, Yuki; Asano, Makoto; Ishii, Kotaro; Kazama, Yusuke; Abe, Tomoko; Fujiwara, Makoto T. (Frontiers in Plant Science, 2024)
Pre-mRNA splicing is a fundamental process in eukaryotic gene expression, and the mechanism of intron definition, involving the recognition of the canonical GU (5'-splice site) and AG (3'-splice site) dinucleotides by splicing factors, has been postulated for the most cases of splicing initiation in plants. Splice site mutations have played crucial roles in unraveling the mechanism of pre-mRNA splicing in planta. Typically, splice site mutations abolish splicing events or activate one or more cryptic splice sites surrounding the mutated region. In this report, we investigated the splicing pattern of the EGY1 gene in an Ar-ion-induced egy1-4 allele of Arabidopsis thaliana. egy1-4 has an AG-to-AC mutation in the 3′-end of intron 3, along with 4-bp substitutions and a 5-bp deletion in adjacent exon 4. RT-PCR, cDNA cloning, and amplicon sequencing analyses of EGY1 revealed that while most wild-type EGY1 mRNAs underwent a single splicing pattern, the egy1-4 mRNAs exhibited multiple splicing defects. Almost a half of EGY1 transcripts represented 'intron retention' at intron 3, while the other half exhibited activation of 3' cryptic splice sites either upstream or downstream of the original 3'-splice site. Unexpectedly, around 8% of EGY1 transcripts in egy1-4 exhibited activation of cryptic 5′-splice sites positioned upstream of the authentic 5'-splice site of intron 3. Whole genome resequencing of egy1-4 indicated that it has no other known impactful mutations. These results may provide a rare, but real case of activation of cryptic 5'-splice sites by downstream 3'-splice site/exon mutations in planta.